The Autoregressive Distributed Lag Method in Predicting Aceh's Economy Post-Special Autonomy Fund - Dian Safitri, Winny; Iqbal Muttaqin, Mohd (Transcendent Journal of Mathematics and Applications, 2022)
Economic growth is a process that reflects the dynamic aspects of an economy that describes the movement of the economy from time to time. Economic growth is one indicator of the success of the implementation of development that can be used as a macro benchmark and can be reflected in changes in Gross Regional Domestic Product (GRDP) in an economy. area. This study was conducted to determine the effect of the Revenue Sharing Fund (DBH) and the Additional Revenue Sharing Fund (TDBH) of oil and gas on the Acehnese economy after the Special Autonomy Fund (SAF) ended from an Islamic economic perspective. The type of research used in this research is quantitative. The method used in this study is the Autoregressive Distributed Lag (ARDL) model. The data used in this study is secondary data sourced from related agencies. The results of this study using the ARDL model show that partially the oil and gas DBH has a negative and significant effect, while the oil and gas TDBH has a positive and significant impact on the Acehnese economy after the SAF ends.